SIMULATION OF DOSE DISTRIBUTION IN VICINITY OF CLOUD OF CONTAMINATED AIR LEAKAGE FROM SEVERE NPP ACCIDENT - Klusoň, Jaroslav; Urban, Tomáš (Radiation protection dosimetry, 2019)
Method of Monte Carlo simulation of gamma radiation fields in the vicinity of the cloud of air contaminated by the radionuclides from emergency leakage from nuclear power plant was designed and tested. Air kerma rates distributions as well as gamma field spectral distributions were calculated for the Gaussian cloud model, different atmospherical conditions and emergency scenarios source terms. Based on this model, the radiation doses in the aerial vehicle (helicopter) and its shielding properties in the radiation fields in cloud vicinity were evaluated with an aim to prepare a method providing data for planning adequate radiation protection of the personnel during airborne monitoring/interventions.
Keywords: záření gama; Radiation Monitoring; Gamma Rays; Fukushima Nuclear Accident; počítačová simulace; lidé; Monte Carlo Method; havárie elektrárny Fukušima; Computer Simulation; Nuclear Power Plants; jaderné elektrárny; radioaktivní látky znečišťující vzduch; monitorování radiace; metoda Monte Carlo; vystavení vlivu životního prostředí; Radiation Dosage; dávka záření; Environmental Exposure; Air Pollutants, Radioactive; Humans